2017
DOI: 10.4103/0378-6323.190875
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous problems in elderly diabetics: A population-based comparative cross-sectional survey

Abstract: Numbness, tingling and burning sensation of extremities, prayer sign, finger pebbling, skin tags, stiff joints and acanthosis nigricans were associated with diabetes mellitus among elderly persons in a village in Kerala.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…Another factor that may contribute to this condition is the use of certain ingredients as allergens such as lanolin, paraben esters, dyes, plants, balm, rubber, nickel and topical therapy. [3,26,27] This study found basal cell carcinoma in 0.…”
Section: This Study Used Primary Data On 80 Patients Who Visited the mentioning
confidence: 63%
“…Another factor that may contribute to this condition is the use of certain ingredients as allergens such as lanolin, paraben esters, dyes, plants, balm, rubber, nickel and topical therapy. [3,26,27] This study found basal cell carcinoma in 0.…”
Section: This Study Used Primary Data On 80 Patients Who Visited the mentioning
confidence: 63%
“…Predisposing factors include trauma, peripheral vascular diseases, immunosuppressive conditions including diabetes. [13] In a study involving elderly diabetecs, [14] the prevalence of tinea pedis was found to be 23%. However, our study revealed a prevalence of 13.4% (males) and 3.2% (females).…”
Section: Discussionmentioning
confidence: 99%
“…3,5 Acanthosis nigricans is common in obese and diabetic patients, therefore it is likely to be associated with acrocordon. 6 In this article, the lesion that we presenteddraws attention with ulcer development in its origin in the axillary region by undergoing traction as the result of gravity depending on the weight of this mass besides it is a giant acrochordon which is a rare form of such lesions.…”
mentioning
confidence: 94%